Universities and economically depressed regions: how strong is the influence of the University of Évora in the regional human capital? - Conceiç\~ao Rego (European Regional Science Association (ERSA), 2004)
Universities are a source of significant multiplier effects upon local and regional economic activity. In the case of economically depressed regions, the importance of universities is enhanced. This is the case of the University of Évora, located in Alentejo (Portugal), one of the poorest EU regions, where it has been a key element to the dynamics of local economic activity. Apart from a direct impact upon the economic activity of Alentejo, the University of Évora has also been promoting demographic effects, both by encouraging new permanent residents to the area, and also by attracting a fluctuating mass of students which usually become residents during the period of time required to obtain their degrees. In this paper a population of former University of Évora students is analysed with the objective of answering questions related to their connections with the city of Évora, and its surrounding areas, after graduation, and also to analyse their impact upon the regional economic activity and their contribution to the improvement of the regional labour force. The University of Évora is also assessed from the perspective of its relationships with other regional agents, in terms of knowledge and innovation transference. It is concluded that one of the main contributions of the University of Évora to the regional economic activity occurs via the employment of its graduates in local and regional schools, enterprises and other institutions. KEY-WORDS: Human Capital, Regional Development, Universities JEL CLASSIFICATION: O15, O18, R12
Keywords: O15; O18; R12; 330